PERENCANAAN BERBASIS DATA DI SEKOLAH: ANTARA MIMPI TRANSFORMASI DAN REALITA IMPLEMENTASI - Sahriah; Arismunandar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT Data-Based Planning (DBP) has been promoted as a new standard for effective school management, promising efficiency and quality improvement through evidence-based decision-making. In Indonesia, this policy has been formalized through platforms such as the Education Report Card (Rapor Pendidikan), which is integrated with school budgeting systems (ARKAS). However, there remains a significant gap between the ideal expectations of DBP and the realities of its implementation in schools, where DBP is often perceived merely as an administrative burden. This article aims to critically analyze this dualism by mapping the efficiency expectations promised by DBP, identifying fundamental implementation challenges, and examining the gap between expectations and realities. This study employs a descriptive qualitative approach using a literature review method, analyzing secondary data from journals and research reports. The findings reveal that DBP theoretically offers managerial efficiency (targeted budget allocation), academic efficiency (precise quality interventions), and accountability efficiency (fact-based transparency). However, real-world implementation shows three major barriers: (1) low data literacy among school personnel, leading to a